Aplikasi Wireless Sensor Network (WSN) Berbasis Radio Frequency (RF) dan SMS Alert GSM - Toni Firnandes; Sumantri K Risandriya; Kamarudin Kamarudin (Politeknik Negeri Batam, 2013)
Monitoring Technology is a system with low cost and high efficiency becomes a challenge in the current era. The author makes a room monitoring system with wireless sensor network (WSN) based radio frequency GSM and SMS Alert. This system consists of two pieces of slave nodes and one master node. Master node and slave nodes using XBee modules as communications equipment. Each slave node consists of a DHT11 sensor to measure the room temperature and humidity, light sensor light dependent resistor (LDR) for measuring the intensity of light, the voltage sensor to measure the voltage source tools and PIR sensor for detecting movement of people in the room. All data sent to each slave node to the master node is processed and displayed. Then when the system is operating in a state of active monitoring, when the movement is detected, the master node will send SMS alerts to the user using a GSM modem wavecom module. Room monitoring results with these systems in accordance with the design, room condition information generated quite accurate with an average error of measurement is not more than 2%. SMS alerts precisely and quickly accepted by the user as soon as movement is detected in the room.